2016
DOI: 10.1016/j.jval.2016.03.1767
|View full text |Cite
|
Sign up to set email alerts
|

Development Of A Linked Database For Cystic Fibrosis Research By Integrating A Patient Registry With Administrative Claims Data

Abstract: Medical Record (EMR) analysis were to understand patient characteristics within current clinical care, to optimize the study design, and to reduce burden on sites and patients. Methods: We conducted an analysis of 11 country-specific EMR data sources (USA,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…There is an increasing interest in understanding health, social and economic consequences of CF beyond what is captured in the registries. This is highlighted by the increasing number of studies linking EHR to other CF Registries , for example to study the economic impact of CF [28] or to address detailed questions relating to in-hospital care of people with CF [29]. In this study, we have shown the importance of using multiple data sources to identify individuals with CF if a gold standard (e.g.…”
Section: Discussionmentioning
confidence: 96%
“…There is an increasing interest in understanding health, social and economic consequences of CF beyond what is captured in the registries. This is highlighted by the increasing number of studies linking EHR to other CF Registries , for example to study the economic impact of CF [28] or to address detailed questions relating to in-hospital care of people with CF [29]. In this study, we have shown the importance of using multiple data sources to identify individuals with CF if a gold standard (e.g.…”
Section: Discussionmentioning
confidence: 96%